Stories of professional development in Brazilian Languages Without Borders Program - Kirsch, William; Sarmento, Simone (BELT - Brazilian English Language Teaching Journal, 2018)
This research has investigated the stories of professional development of five student teachers who participate in a community of teachers of English as an Additional Language in a large research university in the south of Brazil. This community has emerged from the Languages without Borders Program (LwB) and has as its end goal teaching English to the university’s community – faculty, staff and, especially, students. The data was obtained through semistructured interviews with focal participants, who were asked to tell us their story of learning in the community. From the data, it is possible to interpret that participants have developed professionally in their trajectory in the Program through the engagement in a number of practices integral to the community.